Diffusion weighted imaging and relaxometry in abdominal organs - Omar, Nur Farhayu (2016)
This thesis presents the application of diffusion weighted imaging (DWI) and relaxometry MRI studies in three organs in the abdomen, the kidney, colon and liver. These methods are first applied at 1.5 Tesla in healthy volunteers and patients with Cardiorenal Syndrome (CRS), a clinical condition in which cardiac and renal dysfunctions (RD) coexist. Diffusion parameters are determined using the mono-exponential ADC, bi-exponential IVIM, stretched-exponential and Kurtosis models, as well as diffusion tensor imaging (DTI) in order to assess pathophysiology and structural changes in the kidney. Complementary longitudinal relaxation time (T1) mapping and PC-MRI flow measures are collected for comparison with diffusion parameters. The assessment of the colonic content using T1 measures as a biomarker of water absorption and health is presented in the second study. The main objective of the study was to determine the robustness of bi-exponential model in the fitting of T1 in the colonic contents of ascending colon. T1 measurements of colonic content are made at different positions in the ascending colon, before and after a liquid challenge. The reliability of T1 measurements of colonic content were compared across observers. The heterogeneity in the measurements was evaluated by considering different ROI sizes and locations. The final study is the assessment of liver function associated with Chronic Liver Disease (CLD) using DWI and T1 measurement at 1.5 T and a comparison with histological measures. the Measurements of T1 and diffusion parameters (ADC and IVIM) to stratify fibrosis stage in liver disease are combined with T2* measurement of iron accumulation. The repeatability and reproducibility of this protocol is then tested in the healthy liver using MRI at 3T for the assessment of structural and haemodynamic changes for future studies, with an evaluation of the choice of b-values to inform fitting of the bi-exponential (IVIM) model provided.